A política de assistência estudantil e a contrarreforma universitária: estudo sobre o programa de moradia universitária na Universidade Federal do Ceará - UFC - Viana, Mônica Josiane Coelho (2012)
This work aims to analyze The UFC University Housing Program as part of the student assistance policy, inserting it into the process of counter-reform of higher education. Understanding the relevance of this program has been elected as the central objective in the trajectory of student assistance with social rights acquired, observing the relation between the students’ real needs and the services provided by the State. In order to achieve this goal, we started with the analysis of the current global crisis of capital and the implications for the structural adjustment of the State, which has been advancing since the 1990s in Brazil, where we are able to witness an increasing denial of rights to the working class, not to mention the constant privatization of education, especially higher education. The historical periods that include governments of Fernando Henrique Cardoso – FHC e Luiz Inácio da Silva – Lula are highlighted, focusing some of the actions taken in recent history concerning the IFEs, public-private partnerships, PROUNI e REUNI. Then, we try to reconstruct the history of student assistance in Brazil, identifying its origin, advances and setbacks in its implementation, getting to the recent elaboration of the Plano Nacional de Assistência Estudantil – PNAES (National Student Assistance Plan). Once it is done, we step more specifically into the field of student assistance at the Federal University of Ceará – UFC, examining, in a deeper status, the University Housing Program from the department of Student Affairs at UFC. Established in the Historical and Dialectical Materialism, the research, apart from theory and documental materials, also had an application of a questionnaire with 111 resident students from the University Housing Program at UFC in the first half of 2012. The developed studies point to a context in which a systematization of a national student assistance policy occurred quite late in the country, and state the importance of the students’ organized struggle. Besides emphasizing the limitations of the assistance policy before the needs of students, it is defended here the urgency of broadening and strengthening of the policy in the face of growing impoverishment of the working class. The analysis allows us to focus on the promise of democratization of access to higher education through the alleged “mobility” allowed by the examination Enem Sisu.